Classification of zeugmatic constructions - Mahmudova, Nigora (The Lingua Spectrum, 2026)
This article examines the linguistic nature, structural-semantic features, and functional potential of zeugmatic constructions based on materials from the Uzbek and German languages. It discusses theoretical interpretations of zeugma dating back to antiquity, as well as contemporary structural, semantic, pragmatic, and derivational approaches to its investigation. Particular attention is paid to the syntactic center of zeugmatic constructions, its relation to several components, and the semantic heterogeneity that arises from such relations. According to the nature of the predicative center, zeugmatic constructions are classified into verb-centered, noun-centered, and mixed types, while their simple and complex structural varieties are also characterized. The study reveals the role of zeugma in achieving syntactic economy, semantic density, expressiveness, imagery, and pragmatic impact. From a derivational perspective, zeugma is interpreted as a derived syntactic construction resulting from the structural reorganization of syntactic units and the omission of a repeated predicative center.